Two-level game algorithm for multi-microgrid in electricity market - Lin, Yun; Dong, Ping; Sun, Xinglu; Liu, Mingbo (IET renewable power generation, 2017)
The operation mode of microgrids influences the dispatching management of distribution system in the power market. The study uses game theory to study dispatching strategies between multi-microgrid in the distribution system. For this purpose, a two-level game model of multi-microgrid dispatching in the electricity market is proposed. Firstly, the upper level of the model researches the answer of a basic question for a multi-microgrid distribution system that what the boundary line between non-cooperation mode and coalition mode is. Secondly, by the lower level of the model, multi-microgrid decides the operation mode ultimately when it is uncertain in the upper level of model. The upper level is a non-cooperative price game between multi-microgrid and distribution system while the lower level is a cooperative trading loss cost game. In order to optimise multi-microgrid dispatching, an algorithm is proposed to allow microgrids merge or split self-adaptively based on NSGA-II. Simulation result shows that the proposed algorithm can find the Nash equilibrium of the upper level of the model and the optimal operation mode for multi-microgrid in the two-level game, which yields a reduction of 52.7% in coalition mode compared to non-cooperation mode.